Fecal Gluten Peptides Reveal Limitations of Serological Tests and Food Questionnaires for Monitoring Gluten‐Free Diet in Celiac Disease Patients. (October 2016) - Comino, Isabel; Fernández‐Bañares, Fernando; Esteve, María; Ortigosa, Luís; Castillejo, Gemma; Fambuena, Blanca; Ribes‐Koninckx, Carmen; Sierra, Carlos; Rodríguez‐Herrera, Alfonso; Salazar, José Carlos; Caunedo, Ángel; Marugán‐Miguelsanz, J M; et al.
Abstract : Objectives: Treatment for celiac disease (CD) is a lifelong strict gluten‐free diet (GFD). Patients should be followed‐up with dietary interviews and serology as CD markers to ensure adherence to the diet. However, none of these methods offer an accurate measure of dietary compliance. Our aim was to evaluate the measurement of gluten immunogenic peptides (GIP) in stools as a marker of GFD adherence in CD patients and compare it with traditional methods of GFD monitoring. Methods: We performed a prospective, nonrandomized, multicenter study including 188 CD patients on GFD and 84 healthy controls. Subjects were given a dietary questionnaire and fecal GIP quantified by enzyme‐linked immunosorbent assay (ELISA). Serological anti‐tissue transglutaminase (anti‐tTG) IgA and anti‐deamidated gliadin peptide (anti‐DGP) IgA antibodies were measured simultaneously. Results: Of the 188 celiac patients, 56 (29.8%) had detectable GIP levels in stools. There was significant association between age and GIP in stools that revealed increasing dietary transgressions with advancing age (39.2% in subjects ≥13 years old) and with gender in certain age groups (60% in men ≥13 years old). No association was found between fecal GIP and dietary questionnaire or anti‐tTG antibodies. However, association was detected between GIP and anti‐DGP antibodies, although 46 of the 53 GIP stool‐positive patients were negative for anti‐DGP. Conclusions: Detection of gluten peptides in stools reveals limitations of traditional methods for monitoring GFD in celiac patients. The GIP ELISA enables direct and quantitative assessment of gluten exposure early after ingestion and could aid in the diagnosis and clinical management of nonresponsive CD and refractory CD. Trial registration number NCT02711397.